E-CRM as a tool for improving the efficiency of organizations ("Journal "U". Economy. Management. Finance.", 2025)
The article analyzes the features of customer relations (CRM) in modern market conditions through electronic management, which has become an integral part of modern business processes through the rapid development of technology and changing consumer behavior.
Keywords: E-CRM; consumer behavior; marketing communications; competition